Marine Pollution Prevention Policy and Port State Control Enforcement in Indonesia: Implementation Gaps and Regulatory Recommendations - Larsen Barasa; Tri Cahyadi; Marihot Simanjuntak; Irfan Faozun; Chanra Purnama (Department of Marine Engineering, Institut Teknologi Sepuluh Nopember, 2026)
Indonesia, as a signatory to MARPOL 73/78, holds binding international obligations for vessel-source pollution prevention across all six annexes. Port State Control (PSC) is the primary enforcement mechanism for realizing these obligations operationally, yet evidence consistently indicates a wide and persistent gap between regulatory obligation and enforcement practice. This study provides a systematic assessment of marine pollution prevention policy and PSC enforcement in Indonesia through a mixed-methods methodology combining quantitative benchmarking of 4,218 IOMOU PSC inspection records (2019–2024), 44 semi-structured stakeholder interviews, and comparative regulatory framework analysis. Results reveal that Indonesia's PSC performance falls significantly below both IOMOU regional and Paris MoU benchmarks across all key indicators: the detention rate of 4.8% is double the Paris MoU average, mean deficiencies per inspection exceed the Paris MoU figure by 1.97, and a repeat deficiency rate of 38.4% — 23.6 percentage points above the Paris MoU — confirms that enforcement is not generating the corrective response it should. MARPOL Annex IV (sewage) and Annex I (oil) deficiency gaps against Paris MoU benchmarks reach 13.2 and 10.8 percentage points respectively, both classified as critical. Six primary implementation gaps are identified: PSC officer capacity deficit, absence of digital inspection systems, inter-agency coordination failure, inadequate penalties, domestic fleet MARPOL exemptions, and port reception facility insufficiency. An Integrated Marine Pollution Prevention Reform Framework addressing all six gaps through a phased four-pillar architecture is proposed, offering a structured pathway for Indonesia to close its enforcement deficit and fulfill its international maritime environmental obligations.